Identification and Classification of Challenges in Virtual Education Management During Crisis Conditions: A Qualitative Study Using Thematic Content Analysis - Doodman, Parvaneh; Aghapour, Bayram; Hashemi Ardekani, Seyed Javad; Ashraf, Seyed Mahmoud (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: This study aimed to identify and classify the major challenges of virtual education management during crisis conditions from the perspectives of elementary school principals in Lamerd County.Methods and Materials: This qualitative study was conducted using thematic content analysis. The research population consisted of elementary school principals in Lamerd County, Fars Province, during the 2023–2024 academic year. Participants were selected through purposive sampling with maximum variation in terms of gender, managerial experience, and school location. The final sample included ten principals, including six women and four men, with a mean age of 42 years and a mean managerial experience of 4.5 years. Data were collected through semi-structured interviews lasting 45 to 75 minutes. Interviews were audio-recorded with participants’ permission, transcribed verbatim, and analyzed using Braun and Clarke’s six-phase thematic analysis framework. MAXQDA software was used to organize codes and categories. Credibility was enhanced through member checking, triangulation with school documents, peer review, and inter-coder agreement.Findings: The analysis led to the extraction of six main categories: infrastructural and technological challenges, educational challenges, family and social challenges, managerial and organizational challenges, psychological challenges, and adaptive strategies of principals. The findings indicated that weak internet infrastructure, platform inefficiency, shortage of digital devices, and the digital divide formed the basic context of virtual education difficulties. Educational challenges included learning decline, reduced participation, weak assessment, and limited teacher-student interaction. Family and social challenges reflected economic limitations, insufficient parental support, increased family responsibility, and educational inequality. Managerial and organizational challenges included delayed instructions, centralized decision-making, weak supervision, and crisis information management. Psychological challenges included anxiety, digital burnout, and reduced motivation among teachers and students.Conclusion: Virtual education management during crisis conditions is a multidimensional phenomenon shaped by technological, educational, social, organizational, and psychological factors.